2012
DOI: 10.1128/aac.05927-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of MK-7655, a Novel β-Lactamase Inhibitor, in Combination with Imipenem against Carbapenem-Resistant Gram-Negative Bacteria

Abstract: c Carbapenem-resistant bacteria represent a significant treatment challenge due to the lack of active antimicrobials available. MK-7655 is a novel ␤-lactamase inhibitor under clinical development. We investigated the combined killing activity of imipenem and MK-7655 against four imipenem-resistant bacterial strains, using a mathematical model previously evaluated in our laboratory. Time-kill studies (TKS) were conducted with imipenem and MK-7655 against a KPC-2-producing Klebsiella pneumoniae isolate (KP6339) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 15 publications
1
106
0
2
Order By: Relevance
“…The combination of ceftolozanetazobactam has demonstrated synergistic activity in vitro against many ESBL producers and AmpC producers; unfortunately, it is not active against KPC-producing enterobacteria [Titelman et al 2011;Sader et al 2011]. MK-7655 in combination with imipenem has been shown to be effective in vitro against a variety of AmpC-and KPC-producing isolates [Hirsch et al 2012].…”
Section: New Antimicrobial Agentsmentioning
confidence: 99%
“…The combination of ceftolozanetazobactam has demonstrated synergistic activity in vitro against many ESBL producers and AmpC producers; unfortunately, it is not active against KPC-producing enterobacteria [Titelman et al 2011;Sader et al 2011]. MK-7655 in combination with imipenem has been shown to be effective in vitro against a variety of AmpC-and KPC-producing isolates [Hirsch et al 2012].…”
Section: New Antimicrobial Agentsmentioning
confidence: 99%
“…Time-kill studies demonstrated synergy between MK-7655 and imipenem (Fig. 4, compound 9) when tested against KPC-producing K. pneumoniae and carbapenem-resistant strains of P. aeruginosa strains with OprD porin deletions and overexpression of AmpC (160). Pharmacodynamic studies have helped to guide the clinical dosing of the inhibitor combination based on a new modeling index of fluctuating susceptibility over time, defined as time above instantaneous MIC (TϾMIC i ) (161).…”
Section: ␤-Lactamase Inhibitor Combinationsmentioning
confidence: 99%
“…Previous dynamic in vitro experiments (HFIM and one-compartment model) examining regimens against KPC-Kp have not described pharmacodynamic activity past 72 h (13,(37)(38)(39)(40). Therefore, it is remarkable that in the present study, the triple combination that included a polymyxin B burst, meropenem, and rifampin was bactericidal until at least 78 h for KPC-Kp 9A and 30 h for KPC-Kp 27A despite combatting a starting inoculum that was 10 to 1,000ϫ higher than those previously investigated.…”
mentioning
confidence: 99%